The importance of securitization in addressing environmental issue: Case on Freeport's tailing waste - Septyanto Galan Prakoso; Ferdian Ahya Al Putra; Nadia Dian Ardita; Adrian Perdana Murtyantoro; Iim Fatimah Timorria (Sustinere: Journal of Environment and Sustainability, 2023)
Numerous environmental challenges remain unresolved in Indonesia, primarily due to a lack of understanding and limited exposure to the issue. This study discusses a particular case specific about tailing waste resulting from mining activities conducted by Freeport in Papua. This issue may persist without securitization efforts from relevant stakeholders. Interestingly, the key stakeholders in this case are the local community, diverging from the stereotype dominated by NGOs and other private actors. Additionally, this study served as a response to the scarcity of discussion securitization regarding environmental concerns in Indonesia. The research employs qualitative descriptive methods supplemented by a comprehensive literature study, drawing upon publications from the Google Scholar database related to securitization in the context of environmental issues in Indonesia. The finding will be visualized by the VosViewer program. The results of this study show the need for comprehensive discussions surrounding the Freeport tailing waste case. These findings are derived from significant keywords identified in related publications, particularly those related to securitization. In conclusion, the research highlights the importance of securitization by certain stakeholders in addressing particular environmental issues, ensuring that, they receive adequate attention and resolved by responsible actors.